Content forwarding strategy based on ICN architecture in VANET - Lan-lan RUI; Hui GUO; Rui-chang SHI; Hao-qiu HUANG (Tongxin xuebao)
Combining VANET with ICN,a routing building and selecting strategy-SRBS based on vehicular dynamic parameters was proposed.After locating the content nodes through content discovery process,several unicast forwarding paths would be built,which reduces useless traffic compared with a flooding way.By introducing dynamic metrics and LET to routing building and selecting process,SRBS improved the link stability and reliability,which ensured the Data’s successful return.Simulation results show the scheme also improves the time tolerance of routings and makes full use of network cache and reduces delay and routing hops.